New, low mass, bond-coat technology for thermal barrier coating - Silva, Manuel (Cranfield University, 2005)
To remain competitive, gas turbine manufacturers must aim for continuingly improved engine efficiencies and thrust-to-weight ratio. This has resulted in the design of gas turbines with increased turbine entry temperature (TET). Thermal barrier coatings (TBCs) are the most promising systems, which thermally protect engine components and allow their use at higher engine gas temperature by potentially reducing metal surface temperature by up to 150°C. The TBC system consists of a metallic bondcoat and a thermally insulating strain-tolerant ceramic top coat. The bondcoat is a critical part of the system; its failure has a major impact on the lifetime of the TBC. The purpose of this work is the development of a novel and innovative bondcoat with reduced weight, also called "low-mass" bondcoat. This new class of bond coat consisted of a thin (2.5 to 8 J..lm thick) coating containing successive layers (from 9 to 163) of aluminium and platinum. The layers react with one another exothermically by diffusion after a subsequent heat-treatment at a relatively low temperature (700°C), to form an intermetallic bond coat. In this thesis, the manufacture and optimisation of the low-mass bond coat TBC are presented and discussed. Deposition prerequisites along with good deposition practice were defined in order to produce successfully the low-mass bond coat in a clean environment. Stable working parameters were established, among which a roughness working window, as the substrate initial roughness appears to be a key parameter for coating adherence. The structure of the individual as deposited layers were characterised, which allowed to determine the surface temperature during deposition (between 150°C and 350°C). This was well below the temperature above which the exothermic reaction is triggered (400°C). High-multilayered bondcoats (PtAI, PtAh, Pt2Ah stoichiometries) were successfully manufactured, characterised and integrated in a TBC system, among which the thinnest bond coat for THC ever made (51 layers for a 2.5 J..lm thick PtAh). The low-mass bond coat TBC system presented a singular structure consisting of a dense intermetallic layer overlaid by a composite structure of Ah03 precipitates within a (Ni,Pt)xAly matrix. Furthermore the TGO, thermally grown oxide, formed and grew with a typical equiaxed granular structure. This novel TBC system was tested along with commercial coatings under thermal cyclic oxidation, aiming to simulate the thermal cycles induced by the operating aircraft gas turbine .. Regarding to the thickness and the aluminium reservoir of the low mass bond coats, the performances are outstanding, confirming the potentiality of this new type of TBC systems. A degradation mechanism was proposed based on FIB and SEM observations along with chemical analysis. The outstanding performance of the low mass bond coat TBC system is thought to be due to the very specific manufacturing process and its influence on the alumina scale growth under the TBC.